2018
DOI: 10.1089/soro.2017.0076
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Textile Mechanical Anisotropy for Fabric-Based Pneumatic Actuators

Abstract: Knit, woven, and nonwoven fabrics offer a diverse range of stretch and strain limiting mechanical properties that can be leveraged to produce tailored, whole-body deformation mechanics of soft robotic systems. This work presents new insights and methods for combining heterogeneous fabric material layers to create soft fabric-based actuators. This work demonstrates that a range of multi-degree-of-freedom motions can be generated by varying fabrics and their layered arrangements when a thin airtight bladder is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 27 publications
1
128
0
Order By: Relevance
“…Copyright 2013, WILEY‐VCH. f) Operating principle of a textile‐based pneumatic actuator . Reproduced with permission.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2013, WILEY‐VCH. f) Operating principle of a textile‐based pneumatic actuator . Reproduced with permission.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…Pneumatic actuators are a common form of wearable actuation that changes the shape of materials through the flow of air pressure. Recently, Cappello et al reported a textile based pneumatic actuator . Knitted and woven textiles have different strain properties.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…To address this problem in the rigid mechanical robotic systems, soft robots have been developed (Laschi and Cianchetti, 2014). Yap et al (2017) and Cappello et al (2018) have developed the robotic hands by the utilization of soft bending actuators to their bi-directional robotic gloves (Hong et al, 2017), which further reduced their weight and facilitated the performance of ADL, e.g. grasp of a bottle, using the soft robotic gloves.…”
Section: Introductionmentioning
confidence: 99%
“…They combined knitted and woven fabrics, that is, elastic and non-elastic materials, as top and bottom layers around an airtight bladder. 36 More specifically, the top layer was a warpknitted raschel polyamide-elastane textile with preferential strain along the longitudinal direction and with limited lateral stretch, while a plain weave polyamide textile was chosen as bottom layer. In addition, pleats were inserted to further increase the possible curvature in states with different pressure of the airtight bladder inside.…”
Section: Introductionmentioning
confidence: 99%